2012
DOI: 10.1111/j.1369-1600.2012.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

COMT Val158Met modulates the effect of childhood adverse experiences on the risk of alcohol dependence

Abstract: Genetic factors and childhood adverse experiences contribute to the vulnerability to alcohol dependence. However, empirical data on the interplay between specific genes and adverse experiences are few. The COMT Val158Met and DRD2/ANKK1 Taq1A genotypes have been suggested to affect both stress sensitivity and the risk for alcohol dependence. This study tested the hypothesis that genetic variation in COMT Val158Met and DRD2/ANKK1 Taq1A interacts with childhood adverse experiences to predict alcohol dependence. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 102 publications
(127 reference statements)
0
21
1
Order By: Relevance
“…Including these constructs, and expanding the scale should be an area of future research. The scale used herein is one of many ways exposure to trauma in childhood has been correlated with substance use (Young-Wolff, Kendler, & Prescott, 2012; Schilling, Aseltine, & Gore, 2007; Douglas et al, 2010; Kabiru, Beguy, & Ezeh, 2010; Kauhanen, Leino, Lakka, Lynch, & Kauhanen, 2011; Koss et al, 2003; Schellekens et al, 2013; Zlotnick, Tam, & Robertson; 2004; Low et al, 2012; Rothman, Bernstein, & Strunin, 2010; Meara & Frank, 2005), and it is unclear whether these associations would replicate with alternative measures of childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Including these constructs, and expanding the scale should be an area of future research. The scale used herein is one of many ways exposure to trauma in childhood has been correlated with substance use (Young-Wolff, Kendler, & Prescott, 2012; Schilling, Aseltine, & Gore, 2007; Douglas et al, 2010; Kabiru, Beguy, & Ezeh, 2010; Kauhanen, Leino, Lakka, Lynch, & Kauhanen, 2011; Koss et al, 2003; Schellekens et al, 2013; Zlotnick, Tam, & Robertson; 2004; Low et al, 2012; Rothman, Bernstein, & Strunin, 2010; Meara & Frank, 2005), and it is unclear whether these associations would replicate with alternative measures of childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, regression is still commonly used for disease prediction. For example, a search of PubMed revealed 10 articles published in 2013 which applied regression methods for the prediction of a variety of diseases, including cerebrovascular disease, age-related macular degeneration, and hypertrophic cardiomyopathy (Abraham et al, 2013; Borque et al, 2013; Gruner et al, 2013; Harada et al, 2013; Mondul et al, 2013; Romano et al, 2013; Schellekens et al, 2013; Sharma et al, 2013; Tsai et al, 2013; Uddin et al, 2013). In addition, extensions including regression of the whole genome using a Best Linear Unbiased Prediction method (G-BLUP) can produce more highly predictive models (de Los Campos et al, 2013).…”
Section: Utility and Methodsmentioning
confidence: 99%
“…The COMT gene includes a common functional polymorphism Val158Met that is associated with lower COMT enzyme activity and, therefore, reduced dopamine functioning in the prefrontal cortex [44]. In a case control design with male abstinent alcohol-dependent patients and their matched controls (n= 110), researchers found that carriers of the low-activity Met allele (Met/Met or Val/Met) who were exposed to childhood adversity had a higher risk of developing severe alcohol dependence than individuals homozygous for the Val allele [45]. In contrast, the DRD2/ANKK1 Taq1A A1 genotype did not interact with childhood adversity in predicting alcohol dependence [45].…”
Section: Moderators Of Dopamine and Opioid Genesmentioning
confidence: 99%
“…In other cases, genotypes appear to be differentially susceptible to environments rather than reflecting purely risk or protection. Complicating this picture, some gene variants show patterns of differential susceptibility in response to certain environments but confer risk or protection in response to other environments [45,46]. Such mixed findings point to the importance of using formal methods for testing competitive hypotheses about diathesis-stress versus differential susceptibility [66] and careful model specification [67].…”
Section: ])mentioning
confidence: 99%